2019
DOI: 10.3389/fmars.2019.00018
|View full text |Cite
|
Sign up to set email alerts
|

Land Uses Simplified Index (LUSI): Determining Land Pressures and Their Link With Coastal Eutrophication

Abstract: Human activities on land result in the high-level production of nutrients. When these nutrients reach coastal waters, they could drive the eutrophication process. Here we present the Land Uses Simplified Index (LUSI), an easy-to-use tool for assessing continental pressures on coastal waters. This assessment is done by indirectly estimating continental nutrient loads and concentrations, and their influence on coastal waters. LUSI is based on systematic information describing both the land uses that influence co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…The method then presents a forecast of its possible ecological status. In line with the method developed in this study, land uses have been demonstrated to have direct influences on changes in the water quality [54], as well as in the responses of biotic elements [18]. Therefore, as we have demonstrated, they can be used as a proxy to define pressures that are capable of inducing changes in the ecological characteristics of lentic ecosystems.…”
Section: Discussionsupporting
confidence: 54%
“…The method then presents a forecast of its possible ecological status. In line with the method developed in this study, land uses have been demonstrated to have direct influences on changes in the water quality [54], as well as in the responses of biotic elements [18]. Therefore, as we have demonstrated, they can be used as a proxy to define pressures that are capable of inducing changes in the ecological characteristics of lentic ecosystems.…”
Section: Discussionsupporting
confidence: 54%
“…In the case of the North-East Atlantic countries, different pressure indices are used, depending of the BQE, but always including eutrophication parameters, toxicants and hydromorphological pressures ( Borja et al, 2011 ; Lepage et al, 2016 ). In the Mediterranean and Black Seas, most of the assessment methods show relationships with land use, specifically with the Land Uses Simplified Index (LUSI; Flo et al, 2019 ). This index is used as a measure of the total pressure (urban land use, agriculture, rivers, industries) to assess the relationship between assessment methods (usually, phytoplankton, macroalgae and macroinvertebrates) and environmental pressures ( Camp et al, 2015 ; Pinedo et al, 2015 ; Torras et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Land Uses Simplified Index (LUSI) is a method to assess the continental pressures (i.e. mariculture, sewage outfall, harbours, irregular fresh water inputs, sediment nutrient release, urban, commercial and industrial, agriculture) on coastal waters [10,11]. This index has been developed by the Macroalgae Technical Group of the Mediterranean Geographical Intercalibration Group (MEDGIG), as called MA-LUSI (LUSI for shallow water macroalgal communities) [12].…”
Section: Methodsmentioning
confidence: 99%